2018
DOI: 10.5114/polp.2018.77200
|View full text |Cite
|
Sign up to set email alerts
|

Dental problems among hearing-impaired children: Our experiences at a tertiary care teaching hospital in eastern India

Abstract: Aim of the study: To evaluate the prevalence of dental problems in hearing-impaired children at a tertiary care teaching hospital in eastern India. Material and methods: This is a cross-sectional descriptive study carried out on 152 children of dental caries status in the age range 5 to 16 years. The children in this study were divided into group I (5-9 years), group II (10-12 years) and group III (13-16 years). Oral health and treatment were documented using methods and standards following WHO oral health sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The assessment of the risk of bias via New Castle Ottawa Scale for cross sectional studies revealed that all of the studies were reported to be of fair/good quality and were also included in the meta‐analysis. Of the 13 included studies, four studies exclusively assessed dental caries prevalence as their outcome 4,12–14 three exclusively reported dental caries experience 15–17 and six studies reported both dental caries and caries experience 8,9,18–21 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The assessment of the risk of bias via New Castle Ottawa Scale for cross sectional studies revealed that all of the studies were reported to be of fair/good quality and were also included in the meta‐analysis. Of the 13 included studies, four studies exclusively assessed dental caries prevalence as their outcome 4,12–14 three exclusively reported dental caries experience 15–17 and six studies reported both dental caries and caries experience 8,9,18–21 …”
Section: Resultsmentioning
confidence: 99%
“…The maintenance of oral care in hearing impaired children is always challenging and the oral care is most often unattended among the hearing impaired children 4 . Studies in the past have revealed that oral alterations compromise the overall health of individuals and impact their quality of life and well‐being, not only physically but also socially and psychologically 5–7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with hearing impairments need specific consideration when it comes to oral health. Age, the level of hearing loss, and lifestyle variables can all influence dental problems for individuals with hearing disabilities [ 10 , 11 ]. It may be difficult to comprehend or accept responsibly following the preventive dental health routines by these children.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research has consistently demonstrated that individuals with disabilities, including hearing impairment, are more susceptible to dental caries and periodontal conditions due to the challenges they face in maintaining good oral hygiene. (20,21) In this context, this study sought to shed light on the speci c oral health challenges faced by this population in the Karachi region.…”
Section: Discussionmentioning
confidence: 99%